VENTRICULAR FIBRILLATION ARREST IN AN ELDERLY FEMALE DUE TO AMIODARONE-INDUCED ACQUIRED LONG-QT SYNDROME - Mingma Sherpa, DO (Elsevier, 2024)
Therapeutic Area: Pharmacologic Therapy Case Presentation: We report the case of a 77-year-old female who presents after a LifeVest defibrillator shock. She had initially presented a month prior with new-onset heart failure and atrial fibrillation with rapid ventricular response. She was diagnosed with tachycardia-mediated cardiomyopathy. After three unsuccessful attempts at cardioversion, she was started on oral amiodarone 400mg twice a day. On discharge, she was prescribed oral amiodarone 200mg daily, along with entresto, metoprolol succinate, and empagliflozin.She returned a month later after a shock at home. LifeVest interrogation demonstrated polymorphic ventricular tachycardia (VT)/ventricular fibrillation (VF) with prolonged QTc of 712 msec before VT/VF. Laboratory evaluation on admission within normal limits. Initial EKG showed sinus bradycardia with QTc 630 milliseconds (ms). The patient experienced recurrent TdP, requiring defibrillation three additional times while in the emergency department. Cardiac catheterization showed non-obstructive CAD. Amiodarone was held with improvement in her QTc to 398 ms. She was switched to mexiletine 150 mg TID, remained in sinus rhythm, and was discharged with a dual chamber pacemaker and defibrillator for secondary prevention. Background: Due to age-related electrophysiological and structural changes, elderly individuals face an elevated risk of acquired long-QT syndrome (LQTS). Females are at a higher risk than males, with a 1-3% incidence of amiodarone-induced Torsades de Pointes (TdP). Older women taking amiodarone are especially susceptible to proarrhythmic effects, including QT interval prolongation, which can potentially lead to clinical complications. Conclusions: Amiodarone is frequently utilized to treat atrial fibrillation refractory to cardioversion. However, current guidelines are based on studies conducted mainly on middle-aged men with minimal inclusion of women, especially older women, with a lack of sex-specific analysis and reporting. Women are prone to adverse drug reactions, and these reactions may be more severe due to doses that do not consider body weight differences. This can result in higher plasma levels and potential overdosage in women compared to men. Personalizing treatment by identifying sex differences in dosing, efficacy, and safety of cardiovascular drugs may help reduce the rate of adverse effects.